Overexcitabilities as Predictors of Creative ‎Personality among Gifted and Ordinary Students in ‎the State of Kuwait - Al-Gablan, Muneera; Al-Jarrah ‎, Abdelnasser; Al-Abbasi‎, Ahmad (Jordan Journal of Educational Sciences, 2023)
This study aimed to investigate the contributions of overexcitabilities to the creative personalities of gifted and ordinary secondary school students in the State of Kuwait. Furthermore, to determine the significance of the differences in overexcitability and creative personality, according to the student’s classification, gender, and the interaction between them. To achieve the research objectives, the research measures, namely: overexcitabilities, and creative personality, were validated and administered to a sample of 545 secondary school students (545, of whom 176 are gifted and 369 are ordinary), during the second semester of the academic year 2019- 2020. They were selected using the available sampling method (for the gifted) and the cluster method (for the normal). A two-way Anova revealed that there are statistically significant effects of student’s classification on their estimations of creative personality in favor of gifted students, while there is no statistically significant effect of gender, or the interaction between gender and student’s classification on their estimations. A two-way Manova revealed that there is a statistically significant effect of the student’s classification on the student’s practice of overexcitabilities in favor of gifted students, while there is no statistically significant effect of gender or the interaction between gender and the student’s classification on the student’s practice of overexcitabilities. Multiple regression analysis revealed that mental overexcitability contributes to the creative personalities of gifted students while sensory overexcitability contributes to the creative personality of ordinary students. It was observed that the contributions of sensory overexcitability to the creative personality of the gifted students are statistically stronger than those of their counterparts. In light of the results of the study, a similar study might be conducted on different samples, and policy-makers attention might be directed to the inclusion of the research variables in the educational curricula